Comparative study of efficacy of radiofrequency ablation, electrodesiccation, and cryosurgery in the treatment of cutaneous warts - Prashansa Jaiswal; Tapan Kumar Dhali; Paschal D'Souza (Wolters Kluwer Medknow Publications, 2019)
Background: Even though the older and most common treatment for the wart is a destructive method, there is no published randomized control trial comparing the efficacy of radiofrequency ablation, electrodesiccation, and cryosurgery in warts. Objective: The objective of the study is to compare the efficacy and adverse effect of radiofrequency ablation, electrodesiccation, and cryosurgery in the treatment of cutaneous warts. Methods: It was a randomized control trial. Seventy-five patients were randomly divided into three groups of radiofrequency ablation A (Group A), electrodesiccation (Group B), and cryosurgery (Group C) with a sample size of 25 per group by the computer-generated randomized table. Clinical cases of common and plane warts with age >12 years were included in the study. The assessment was based on the reduction of the total surface area of the reference lesion(s), pigmentation, scarring, reappearance of dermatoglyphics, and patient's satisfaction. Results: Complete cure in Group A was 22 (95%), in Group B was 17 (73%), and in Group C was 14 (58%) which was statistically significant (P ≤ 0.001). Majority (>90%) of the patients were very much satisfied with treatment outcome, particularly with radiofrequency which was statistically significant (P = 0.001). Conclusion: Radiofrequency was seen to have the highest cure rate.